MORPHOLOGICAL IDENTIFICATION OF ARBUSCULAR MYCHORRIZAL FUNGI ISOLATED FROM THE RHIZOSPHERE OF Jatropha gossypiifolia L. IN TAMBORA INDONESIA - Nizar, Wahyu Yuniati (Jurnal Silva Samalas, 2026)
The morphological analysis allows identifying the characteristics of AMF spores, while molecular analysis identifies the species and taxonomy position. Thus, both methods are necessary to create a complete and successful taxonomy of AMF. Soil samples taken under Bellyache bush stands in Tambora, Dompu West Nusa Tenggara Indonesia (08˚26’50,278” S and 117˚59’1,999” E). Root sample taken randomly ± 1 g/sample then washed until clean and put in a bottle film. In summary, the roots are cleaned of cytoplasm with 10% KOH solution, then acidified with 1% HCl solution and then stained with 0.05% trypan blue. The results of calculating the percentage of root colonization show that the characteristics of each different mycorrhizae give percentages various colonization. Colonization percentage each the samples experienced differences, namely at P1 25%, P2 40%, P3 50%, P4 40%, P5 60%, P6 55%, P7 100%, P8 35%, P9 55% and P10 25%. Colonization percentage values on the root is moderate. The percentage is affected by circumstances location, such as litter thickness and soil color. On Tambora, Dompu District locations have a thin litter thickness and color reddish brown soil indicating level high levels of iron (Fe). Based on the results of research conducted then it can be concluded that the Genus of spores found at the research location both on soil samples and roots namely Glomus, Acaulospora and Gigaspora. Glomus spores have relative abundance highest. Percentage of mycorrhizal colonization in Tambora Dompu District is classified as moderate.